Effects of mobility training on severe burn patients in the BICU: A retrospective cohort study. Issue 7 (November 2016) - Deng, Huan; Chen, Jian; Li, Frank; Li-Tsang, Cecilia W.P.; Liu, Qiushi; Ma, Xiaohong; Ao, Ming; Chen, Nan; Zhou, Yaqin; Zhong, Xiaoyun; Chen, Zhiyu; Cao, Lei; et al.
Highlights: Mobility training is feasible and effective. Goal-oriented ADL training is recommended for severe burn patients in the future. There is necessity to establish standard protocol of early rehabilitation. Abstract: Purpose: To assess the effects of mobility training on severe burn patients in the Burn Intensive Care Unit (BICU). Methods: This was a retrospective cohort study. Severe burn patients with equal to or more than 50% Total Body Surface Area (TBSA) burns who received early rehabilitation in the BICU were included in this study. Based on the different early rehabilitation strategies during the two periods, patients admitted to the BICU from January 2011 to April 2013 were identified as the passive training cohort ( n = 49) while patients admitted to the BICU from May 2013 to December 2013 were identified as the mobility training cohort ( n = 24). Data on length of BICU stay, length of hospital stay, length of rehabilitation in the BICU, ventilator dependent days, strict bed rest time, range of motion (ROM), the Barthel Index (BI) and the Functional Independence Measure (FIM) were collected. Results: Compared with the passive training cohort, patients in the mobility training cohort had significantly shorter length of BICU stay ( p = 0.002), length of hospital stay ( p = 0.010), strict bed rest time ( p < 0.001) and length of rehabilitation in the BICU ( p = 0.026) with improved ROM of shoulder, wrist, hip, knee and ankle joints. Conclusions: Mobility training in the BICU was shown to be feasible and effective in achieving better outcomes than passive training for severe burn patients.